Remoção de fenol de efluente de papel e celulose utilizando microfiltração seguindo de foto-fenton - Prestes, Ana Paula Bacchiega (2018)
The present study evaluated the treatment of paper and cellulose effluent through microfiltration filter membranes followed by an advanced photo-Fenton oxidative process aiming at the removal of phenol. The tests were carried out in laboratory scale and was composed of two stages, the first in microfiltration pilot equipment in order to determine the ideal operational condition for membrane tested. Subsequently, the efficiency of the microfiltration membrane was evaluated in its capability of color removal, phenol, turbidity and total suspended solids (TSS), as well as the permeate flux obtained. The second step was performed in a bench reactor to determine the ideal conditions of iron concentration and hydrogen peroxide for the photo-Fenton process. The effluent degradation efficiency of the post-filtration effluent applied to the photo-Fenton process was then evaluated for complementary removal of color, phenol and COD. The results indicated that the microfiltration membrane worked best at lower pressures (0.5 bar) where it obtained higher flow. This process significantly improved the quality of the raw effluent, obtaining color removal was 94.2%, phenol 56.2%, turbidity 99.8% and 91.01% for SST. Even with high removal values, the effluent is not yet suitable for launching, requiring the use of a posttreatment. Using the photo-Fenton process after microfiltration the results indicated removals of 87.8% for color, 100% of phenol and 90.7% for COD. Thus, the use of the two combined treatments achieved excellent results, bringing the effluent appropriate for launch, and eliminating the present phenol pollutant.